Etiological profile and clinical characteristics in fulminant hepatic failure in North India - Nabi, Tauseef; Rafiq, Nadeema; Arifa, Quratul Ain (International Journal Of Community Medicine And Public Health, 2019)
Background: Acute liver failure (ALF) is a rare but severe, life-threatening, multisystemic medical emergency. ALF of duration <8 weeks in a patient is considered as fulminant hepatic failure (FHF). Its rapid progression and high mortality demand early diagnosis and expert management. Clinical and etiological profile varies with geographical area and time. The objective of this prospective study was to determine the clinical characteristics and etiological profile of FHF. Methods: A total of eighty consecutive patients with a diagnosis of FHF were included in the study. The variables evaluated were demographic, signs and symptoms, biochemical parameters (bilirubin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), prothrombin time (PT), internal normalization ratio (INR) etc.) and etiological profile. Results: Most of the patients were <35 years of age and males. Viral hepatitis 35 (43.8%) was the most common cause of FHF but the majority of the patients 25 (31.2%) had undetermined etiology. Among viral causes, acute hepatitis E was most common followed by hepatitis B and A. Drug or toxic induced liver failure (18.8%) also contributed a significant proportion of cases. The three groups (viral, drug-induced and indeterminate) were comparable for the various baseline characteristics (bilirubin, alanine aminotransferase, INR, creatinine, albumin, grade of encephalopathy, MELD score etc.). Conclusions: Like the rest of India, viral hepatitis was the common cause of FHF but the majority of the patients 25 (31.2%) had undetermined etiology. Our study highlights the differences in the profile of FHF from other earlier studies in India and the west. Each different etiology leads to a similar final common pathway. Trying to determine etiology is essential, however, as outcomes and the use of antidotes depend on the identification of the causative process.